2019 41st Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2019
DOI: 10.1109/embc.2019.8857945
|View full text |Cite
|
Sign up to set email alerts
|

EEG Based Analysis of Cortical Activity during Mirror Visual Feedback Target-Directed Movement

Abstract: In mirror visual feedback (MVF) based rehabilitation, the illusion of mirror reflection of volitional movement of non-paretic limb tends to have a modulatory effect on visuomotor and sensorimotor brain activations. This paper presents EEG based analysis of hemispheric activation asymmetry within the beta band (15-28 Hz) when MVF is combined with a target-directed hand motor task in a block design versus a similar task without any target requirements. MVF coupled with targetdirected movement was associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…A bilateral alpha ERD in response to unilateral MVF movements started 0,5 s before the movement onset and lasted up to 1,5 s after that onset. The same temporal evolution has been demonstrated for the EEG central beta suppression 162 . These outcomes coincide with the temporal dynamics observed in Study I, describing an anticipatory suppression of the central alpha oscillation starting 1 s before the auditory cue triggering the movement up to more than 1 s after that cue.…”
Section: Temporal Features: Anticipation and Execution Of Mvf Illusionsupporting
confidence: 74%
See 1 more Smart Citation
“…A bilateral alpha ERD in response to unilateral MVF movements started 0,5 s before the movement onset and lasted up to 1,5 s after that onset. The same temporal evolution has been demonstrated for the EEG central beta suppression 162 . These outcomes coincide with the temporal dynamics observed in Study I, describing an anticipatory suppression of the central alpha oscillation starting 1 s before the auditory cue triggering the movement up to more than 1 s after that cue.…”
Section: Temporal Features: Anticipation and Execution Of Mvf Illusionsupporting
confidence: 74%
“…As mentioned above, EEG can be used to map the scalp distribution of the alpha and beta band oscillations in response to sensory-motor events. In this context, the majority of the EEG studies observed a clear activity in the sensory-motor area ipsilateral to the moving limb and contralateral to the mirror illusion 72,74,160 or reduced asymmetry in the hemispheric activation at the central electrode sites (C3 or C4) [62][63][64]157,162 . In a comprehensive study, Al-Wasity and colleagues investigated the functional cortical domains related to the comparison of bimanual or unimanual+MVF tasks 74 .…”
Section: Cortical Correlates Of Mvf Illusory Movementsmentioning
confidence: 99%
“…Although many studies reported the ability of MVF on balancing hemisphere asymmetry and modulating hemispheric activation ( Rossiter et al, 2015 ; Bartur et al, 2018 ; Rohafza et al, 2019 ; Zhang and Fong, 2019 ), its effect on shifting network metrics is rarely reported. Thus, as an additional measure, the hemispheric asymmetry in metrics was analyzed for future study.…”
Section: Methodsmentioning
confidence: 99%
“…Although many studies reported the ability of MVF on balancing hemisphere asymmetry and modulating hemispheric activation (Rossiter et al, 2015;Bartur et al, 2018;Rohafza et al, 2019;Zhang and Fong, 2019), its effect on shifting network metrics is rarely reported. Thus, as an additional measure, the 1 https://www.nitrc.org/projects/bct/ hemispheric asymmetry in metrics was analyzed for future study.…”
Section: Hemispheric Asymmetry Analysismentioning
confidence: 99%